La armonización de las acciones tutelares de los derechos de propiedad intelectual en el Ecuador - Naranjo Santander, María de Fátima (2016)
Intellectual property is a branch of law that is governed by a set of rules aimed at protecting, through guardianship proceedings, the rights previously granted on intellectual creations (creations of the mind such as, for example, inventions). These creations are not physical, in fact, they lack materiality. The intellectual property rights are of paramount importance for the economy and development of the States, and, in this regard, for the development of the inhabitants of each State. Legal protection provides the best means to demand respect for this rights, and exercise them if they had been violated or if there is a risk of vulneration. In this context, each State must guarantee the protection of this rights, and adequate procedures to be executed against any infringement of the mentioned rights. Ecuador has the obligation to protect intellectual property, due to the international instruments that has signed. In this line of thought, this paper seeks to establish, analytical and comparatively, if the Ecuadorian State is or is not in compliance with binding international obligations on intellectual property. And, for this matter, intellectual property as a branch of law will be studied, as well as the binding international treaties for Ecuador in the matter, and the internal regulations -including a bill named “Code of Social Economy of Knowledge, Creativity and Innovation", that is being analyzed by the National Assembly. In this regard, and once the analysis and comparison has been made, the main proposal will be to harmonize the Ecuadorian law, in accordance with the aforecited international instruments. In order to prevent the Ecuadorian State of being sanctioned due to the non-compliance of the international instruments, and supranational regulations of the matter.